2022
DOI: 10.1088/1741-4326/ac74d3
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the fusion energy gain factor in magnetic confinement fusion due to plasma temperature anisotropy

Abstract: In magnetic confinement fusion (MCF), the plasma always exhibits an anisotropic temperature distribution, which may impact not only the plasma dynamics but also the nuclear reaction process. Here, through theoretical derivations and self-consistent particle-in-cell simulations with the newly-developed nuclear reaction and alpha particle energy deposition calculation modules, we find that, if considering the plasma has an anisotropic temperature distribution, the fusion energy gain factor ($Q$) of MCF is signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…It can be seen that for all four of these fusion reactions, the enhancements only occur at low temperatures, such as the critical temperatures for D-T, D-D, D-He3, and p-B11, which are around 15 keV, 50 keV, 60 keV, and 140 keV, respectively. Similar conclusions have been drawn in previous studies, as reported in [15,[17][18][19]. The reason for this can be found by examining the cross section plot (figure 1) and the kernel function K(E).…”
Section: Potential For Increased Reactivitysupporting
confidence: 89%
See 2 more Smart Citations
“…It can be seen that for all four of these fusion reactions, the enhancements only occur at low temperatures, such as the critical temperatures for D-T, D-D, D-He3, and p-B11, which are around 15 keV, 50 keV, 60 keV, and 140 keV, respectively. Similar conclusions have been drawn in previous studies, as reported in [15,[17][18][19]. The reason for this can be found by examining the cross section plot (figure 1) and the kernel function K(E).…”
Section: Potential For Increased Reactivitysupporting
confidence: 89%
“…For example, for T 1 → 0 and v d2 = 0, the result reduces to a beam-target case [8][9][10]. If considering only the beam in the same direction, equation ( 8) can be reduced to the results in [3,16,18]. If E d = 0, equation (8) reduces to equation (5).…”
Section: Several Existing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To simulate the nuclear reaction occurs in plasma, a selfconsistently extended nuclear reaction calculation module, the two-body reactions between macro-particles within each cell are considered in the PIC code, which yields alpha particles with weight [35],…”
Section: Verification By Pic Simulationmentioning
confidence: 99%
“…With the development of high-field magnets, it plays an important role in the fields of magnetic confinement nuclear fusion [1]- [3]. The reliability of coil insulation directly affects the safe and stable operation of the device and the stability of the entire system [4].…”
Section: Introductionmentioning
confidence: 99%